2022
DOI: 10.9734/ijecc/2022/v12i130697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Crop Residue Incorporation, Biofertilizers on Nutrient Uptake, Yield of Chickpea (Cicer arietinum L.)

Abstract: The investigation was laid out on clay loam soil at Agricultural Research Station, Adilabad during rabi, 2020 with the aim to understand the chickpea crop performance with residue incorporation and use of biofertilizers along with varied NP recommended doses (0,50,75 and 100%). Results, revealed that, i.e., application of  fertilizers i.e., 20:50:20 kg ha-1 N: P2O5:K2O recorded significantly higher grain yield (2558 kg ha-1) and stover yield (3255 kg ha-1) among all the treatments. Significantly superior nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…However, treatment T2 (100% RDF) accumulated highest K in grain with a mean value of 0.60%, which was only treatment found ignificantly superior over control. Similar findings was reported by Dhegavath et al [36]. Nitrogen and potassium content in stover did not differ significantly by the application of bio-stimulants, as well as by chemical fertilization.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, treatment T2 (100% RDF) accumulated highest K in grain with a mean value of 0.60%, which was only treatment found ignificantly superior over control. Similar findings was reported by Dhegavath et al [36]. Nitrogen and potassium content in stover did not differ significantly by the application of bio-stimulants, as well as by chemical fertilization.…”
Section: Resultssupporting
confidence: 91%
“…Highest stover yield (1342.27 kg ha -1 ) was recorded in treatment T2 where 100% RDF was applied, followed by treatment T7 (1087.33 kg ha -1 ) where 50% RDF was applied along with bio-stimulants at 1:200 dilution level. Similar findings was also observed by Dhegavath et al [36]. Population of bacteria in rhizosphere soil was analysed at 45 and 60 days after sowing.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Vasanthi and Subramanian [8] observed that the highest grain yield and crude protein N, P, and K concentrations and uptake were recorded with the application of vermicompost at 2 t ha -1 along with 100 percent recommended levels of N, P, and K. Mahetele et al [9] reported that the addition of FYM at 10 t ha -1 to soil improved the supply of plant-available nutrients and brought about a favorable soil environment, which ultimately increased the nutrient and water holding capacity of the soil for a longer period and improved the plant dry matter. Similarly, Dhegavath et al [10] reported that all growth parameters, that is, plant population, plant height, dry matter production, total number of pods, test weight, seed yield, stover yield, and harvest index, were significantly higher under soybean residue incorporation with the treatment that received 100% RDF. However, it was found on par to treatment of 75% RD of N plus biofertilizers and 75% RD of P plus biofertilizers along with 50% RD of N plus biofertilizers and 75% RD of P plus biofertilizers.…”
Section: Introductionmentioning
confidence: 88%